Aid for Trade: an opportunity to increase fruit and vegetable supply - Anne Marie Thow; Shishir Priyadarshi (The World Health Organization, 2013)
Low fruit and vegetable consumption is an important contributor to the global burden of disease. In the wake of the United Nations High-level Meeting on Non-Communicable Diseases (NCDs), held in September 2011, a rise in the consumption of fruits and vegetables is foreseeable and this increased demand will have to be met through improved supply. The World Health Organization, the Food and Agriculture Organization and the World Bank have highlighted the potential for developing countries to benefit nutritionally and economically from the increased production and export of fruit and vegetables. Aid for Trade, launched in 2005 as an initiative designed to link development aid and trade holistically, offers an opportunity for the health and trade sectors to work jointly to enhance health and development. The Aid for Trade work programme stresses the importance of policy coherence across sectors, yet the commonality of purpose driving the Aid for Trade initiative and NCD prevention efforts has not been explored. In this paper food supply chain analysis was used to show health policy-makers that Aid for Trade can provide a mechanism for increasing the supply of fruits and vegetables in developing countries. Aid for Trade is an existing funding channel with clear accountability and reporting mechanisms, but its priorities are determined with little or no input from the health sector. The paper seeks to enable public health policy-makers, practitioners and advocates to improve coherence between trade and public health policies by highlighting Aid for Trade's potential role in this endeavour.